Automatic Temperature Analysis of an Image Sensor using an Application in a Semiconductor Industry - Chanathip Wongsomboon; Noppadol Maneerat; Jakkrit Thudthong; Sutikamon Sukasem; Kuniaki Yajima; Bundit Pasaya (My University, 2024)
Manufacturing process improvement is a way to increase the efficiency of production in the process even further. This research is used to change the current work method where employees download oven temperature data of the image sensor in manual CSV file format to analyze and make reports in graph form. The window application is created the data to get the data from the PLC control machine to record temperature data from a CSV file and record it in the SQL database automatically. The web application is also developed to serve as a dashboard for data analysis. It is possible to reduce operating time by 91 percents and can reduce the cost of hiring employees.
Keywords: Sensor Technology and Measurement Systems; Wireless Sensor Networks for Data Analysis; Neural Networks and Applications